OUTCOMES OF LAPAROSCOPIC SURGERY FOR MID-RECTAL CANCER AFTER LONG-COURSE NEOADJUVANT CHEMORADIOTHERAPY AT 108 MILITARY CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
ABSTRACTObjective: To evaluate the early outcomes of laparoscopic surgery for mid-rectal cancer after long-course neoadjuvant chemoradiotherapy at 108 Military Central Hospital.Subjects and methods: This was a retrospective descriptive study conducted on 85 patients with mid-rectal cancer who underwent long-course neoadjuvant chemoradiotherapy followed by radical laparoscopic surgery at 108 Military Central Hospital from August 2018 to August 2023.Results: The main surgical procedure was total mesorectal excision (85.9%), followed by intersphincteric resection (8.2%). Lateral pelvic lymph node dissection was performed in 9.4% of cases. Intraoperative complications occurred in 4.8% of patients. The conversion rate to open surgery was 3.5%. The mean operative time was 126.3 ± 29.4 minutes. Early postoperative complications occurred in 12.9% of cases, most commonly urinary retention (4.7%), anastomotic leakage (2.4%). No early postoperative mortality. The mean postoperative hospital stay was 10.4 ± 5.4 days.Conclusion: Laparoscopic surgery for mid-rectal cancer after long-course neoadjuvant chemoradiotherapy is feasible and safe, with acceptable rates of conversion to open surgery, intraoperative complications, and early postoperative complications.
Keywords: mid-rectal cancer, long-course neoadjuvant chemoradiotherapy, laparoscopic surgery, early outcomes